2006
DOI: 10.1375/pplt.13.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Status of Former Refugee Detainees From the Woomera Detention Centre Now Living in the Australian Community

Abstract: The impact of detention on psychological status, and quality of life was examined in a sample of 150 former refugee detainees from the Woomera Detention Centre now living in the Australian community. Detainees completed a Psychological status inventory including the Truncated Firestone Assessment of Self-destructive Thoughts (T-FAST),the Quality of Life Inventory, the Suicidal Ideation Scale, and the Profile of Mood States,. Former detainees reported their current status; and retrospectively reported their sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Three studies measured the quality of life of detainees and uniformly reported low quality of life ratings, particularly across psychological domains [ 40 , 42 , 46 ]. One of these studies found that levels of quality of life were mediated by the level of perceived support and satisfaction with the care received from detention staff [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies measured the quality of life of detainees and uniformly reported low quality of life ratings, particularly across psychological domains [ 40 , 42 , 46 ]. One of these studies found that levels of quality of life were mediated by the level of perceived support and satisfaction with the care received from detention staff [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six psychological questions Authorised telephone interpreters (used by 77 participants) Robjant et al [ 11 ] Cross-sectional, comparison survey N = 67 detained asylum seekers, N = 30 detained former prisoners, N = 49 asylum seekers living in the community Detention Duration: unknown Unknown UK PTSD, depression, anxiety HADS, IES-R, PDS English Rojas-Flores [ 57 ] Cross sectional comparison survey N = 39 children of detained or deported parents N = 42 unauthorised no history of detention or deportation N = 16 Legal permanent resident Detention Duration: unknown Mexico or Central America US PTSD, depression, behavioural difficulties, daily functioning UCLA PTSD-RI, CES-DSC, BASC-2 PRS-C, TSCYC-SP, BASC-2 TRS-C, CAFAS Rothe et al (2002a) Cross sectional survey N = 74 adolescents Detention Duration: 4-6 months Cuba US PTSD, psychological distress PTSDRI, checklist of PTSD symptoms Rothe et al (2002b) Cross sectional survey N = 87 adolescents Detention Duration: mean 6-8 months Cuba US PTSD, behavioural difficulties PTSDRI, CBCL-TRF Sen et al [ 45 ] Observational, Cross-sectional N = 101 male detained in immigration removal centre Detention Duration: unknown 27 different countries UK Neurodevelopmental MINI v6, SAPAS, AQ-10, ASRS, LDSQ, CANFOR No interpreters Sobhanian et al [ 42 ] Cross-sectional survery N = 150 former refugee detainees Detention Duration: mean 11.3 months, range 2 – 21 months Iran, Afghanistan Australia Psychological status and quality of life T-FAST, QOLI, POMS, SIS Translated and back translated into Farsi, self report administered under supervision of clinical psychologist Steel et al [ 23 ] Cross-sectional N = 10 families (14 adults, 20 children) held for in immigration detention for more than two years Detention Duration: mean 2 years 4 months, rang...…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Steel et al [ 23 ] highlighted that while none of their adult participants reported persistent suicidal ideation prior to detention, at the time of assessment, almost all (93 %) had experienced persistent thoughts of suicide, and a third had harmed themselves. Consistent with these results, Sobhanian et al [ 21 ] found a significant reduction in self-harm and suicidal ideation after refugees had been released. Some scholars have emphasized the political nature of these acts, not merely reducible to an expression of desperation [ 31 ].…”
Section: Discussionmentioning
confidence: 55%
“…In particular, investigation conducted in Australia [ 13 , 20 , 23 , 24 , 26 , 29 ], as well as in UK [ 15 , 25 ], and in Japan [ 19 ] have demonstrated that M-RD causes the mental health of asylum seekers to deteriorate, and that this deterioration - mainly measured in terms of symptoms of post-traumatic stress disorder, anxiety, and depression - is greater the longer the time in detention [15, 28; 29]. Moreover, high rates of suicide (completed and attempted) and self-harm among detainees have been revealed [ 16 , 21 , 23 , 29 , 56 , 57 ]. In particular, Steel et al [ 23 ] highlighted that while none of their adult participants reported persistent suicidal ideation prior to detention, at the time of assessment, almost all (93 %) had experienced persistent thoughts of suicide, and a third had harmed themselves.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 277). Sobhanian, Boyle, Bahr, and Fallo (2006) reported that mean scores on the POMS subscales (except for Vigor) were significantly elevated when refugees were incarcerated in the Woomera Detention Centre, and subsequently declined following their release into the Australian community. …”
Section: Criterion/predictivementioning
confidence: 99%